An interlude in navigation: Submarine signaling as a sonic geomedia infrastructure. (November 2022) - Borbach, Christoph
A closer look into the history of maritime geomedia reveals a historical intermezzo in which navigation in cases of unstable sight was realized with "Submarine Signaling" (SS). This infrastructure for the purpose of safe wayfinding along coasts operated from around 1900 to the early 1920s, relying upon submarine bells in the global oceans, and hydrophones and telephonic user interfaces in vessels. SS can be regarded as a starting point to the era of electrotechnological navigation, and is of media-historical interest insofar as its operability was based on undersea acoustics: shifting its epistemic focus from sight to sound, SS thus lay beyond the "visual regime" that characterizes our current digital geomedia cultures. Herein, I will reconstruct the genesis and history of SS, use it as a contrasting foil to our postmodern geomedia practices, and finally argue for an understanding of geomedia as historically variable phenomena.